A Welfare Analysis of Employment Contracts with and without Asymmetric Information - Hosios, Arthur J. (Review of Economic Studies, 1984)
This paper provides a complete characterization of the welfare economics of employment contracts when workers are immobile in the ex post period. Necessary and sufficient conditions for constrained Pareto optimality are derived for economies with incomplete risk markets, two consumption goods and random production technologies in which: (a) workers can/cannot observe realizations of their employers ' revenue function (symmetric vs. asymmetric information), and in which; (b) employment contracts allow/preclude contingent wages and/or employment levels (flexible vs. rigid contracts). This taxonomic approach serves to identify the welfare implications of exogenous and endogenous contractual rigidities, and to isolate a class of externalities that is unique to economies with asymmetric information. The latter market failure is also present with "indexed " contracts when workers alone can observe realizations of their consumption goods prices (another form of asymmetric information). 1.